Pengaruh Latihan Small Side Games Terhadap Kemampuan Dribbling Pada Pemain Futsal Laskar Kabupaten Sorong - Falentina Karma, Farida; Anwar, Saiful; Pratama, Leo (Jurnal Muara Olahraga, 2024)
This research was motivated by LASKAR players who often made passing errors. In the match, only half of the total passes made were successful. The aim of this research is to determine the effect of small sided games training on passing skills in Laskar players. This research method is a quasi-experimental, one group pretest-posttest design with 16 treatments (Tjalik Sugiardo, 1999: 25). The instrument used was a lowball passing test from Subagio Irianto (1995) which was retested and adapted for the futsal passing test by Dica Febri Wardana (2015: 32) with a validity of 0.710 and a reliability of 0.703. The research subjects were 20 Laskar players, sampling was taken using purposive sampling. The data analysis technique uses hypothesis testing with t test analysis. The results of the research obtained a calculated t value (4.358899) > t table (1.729), showing that "There is an influence of small sided games training on students' passing skills among Laskar players". The pretest mean was 6.1 and the posttest was 7.1, so the mean difference was 1. This shows a better change of 16.39%.